2022
DOI: 10.3390/foods11182759
|View full text |Cite
|
Sign up to set email alerts
|

Resistant Protein: Forms and Functions

Abstract: Several global health risks are related to our dietary lifestyle. As a consequence of the overconsumption of ultra-processed and highly digestible protein (150–200% of the recommended value), excess dietary proteins reach the colon, are hydrolysed to peptides and amino acids by bacterial proteases and fermented to various potentially toxic end products. A diet reformulation strategy with reduced protein content in food products appears to be the most effective approach. A potential approach to this challenge i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 61 publications
1
1
0
Order By: Relevance
“…Food & Function more convoluted in the context of legume proteins, where their affinity for iron is coupled with structures and regions that exhibit hydrolytic resistance against digestive enzymes and brush border amino peptidases. 28 Several legume proteins have been shown to inhibit fortified iron solubility, hence bioavailability, in vivo, 29,30 which are consistent with our findings from the native pea protein (PPI). This digestion-resistant fraction containing both legume protein and fortified iron reaches the lower gut, although their combined effects on colonic microbiome markers have been unexplored until this study.…”
Section: Papersupporting
confidence: 88%
“…Food & Function more convoluted in the context of legume proteins, where their affinity for iron is coupled with structures and regions that exhibit hydrolytic resistance against digestive enzymes and brush border amino peptidases. 28 Several legume proteins have been shown to inhibit fortified iron solubility, hence bioavailability, in vivo, 29,30 which are consistent with our findings from the native pea protein (PPI). This digestion-resistant fraction containing both legume protein and fortified iron reaches the lower gut, although their combined effects on colonic microbiome markers have been unexplored until this study.…”
Section: Papersupporting
confidence: 88%
“…Several studies have reported that resistant proteins are resistant to digestive enzymes and behave as dietary fibers, similarly to cellulose, pectin, gum, and lignin [31,32]. Additionally, resistance proteins have been reported to influence the gut microbiota [18].…”
Section: Discussionmentioning
confidence: 99%